1975
DOI: 10.1002/1097-0142(197506)35:6<1558::aid-cncr2820350613>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiation tolerance of the spinal cord

Abstract: A series of nine cases of radiation myelopathy seen at the University of California, San Francisco (UCSF) is reviewed, and their treatment data converted into nominal single doses (NSD) and equivalent single doses (ED). The 1% incidence level of myelopathy in the thoracic cord is 1015 rets (ED), and the 50% incidence level is 1476rets (ED). Caution should be used when utilizing a rapid fractionation schedule; it appears that 2000 rads in 5 fractions and 3000 rads in 10 fractions is a safe regimen for the tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
54
0
4

Year Published

1978
1978
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(59 citation statements)
references
References 11 publications
1
54
0
4
Order By: Relevance
“…On the other hand, LG astrocytomas are slow growing tumors and radiotherapy may not be as effective on tumor cells which are currently not undergoing mitosis [26]. Furthermore, radiation tolerance of spinal cord is limited, particularly in the presence of an intrinsic tumor, which makes the tissue more vulnerable to injury [35,44,71]. Long-term survivors treated with mere biopsy and external decompression were reported in some studies [20,27,56].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, LG astrocytomas are slow growing tumors and radiotherapy may not be as effective on tumor cells which are currently not undergoing mitosis [26]. Furthermore, radiation tolerance of spinal cord is limited, particularly in the presence of an intrinsic tumor, which makes the tissue more vulnerable to injury [35,44,71]. Long-term survivors treated with mere biopsy and external decompression were reported in some studies [20,27,56].…”
Section: Discussionmentioning
confidence: 99%
“…Medulla spinalis gibi yavaş prolifere olan dokularda geç etkiler çoğun-lukla kalıcı hasarlara neden olur. [2,3,[6][7][8] Yasui ve ark. RM'sini klinik spektruma göre dört kategoriye ayırmışlardır: a) Akut parapleji veya kuadripleji, b) Alt motor nöron bulguları, c) Akut geçici RM, d) Kronik progresif RM.…”
Section: Discussionunclassified
“…Günlük radyasyon dozu, total doz, radyoterapi alanı, lineer enerji transferi, eşzamanlı veya ardışık kemoterapinin uygulanması, kemik iliğini etkileyen kemoterapotiklerin verilmesi, ışın alanına giren medulla spinalisin uzunluğu gibi faktörler miyelopatinin oluşumunu ve şiddetini etkilemektedir. [1][2][3] Nörolojik problem, geçici ve kronik-progresif olmak üzere iki formda görülür. En sık görüleni geçici miyelopatidir.…”
unclassified
“…There is also no published experience regarding the tolerance of the human spinal cord to such single-fraction doses. In a review evaluating 172 patients who underwent cervical and thoracic fractionated radiotherapy at the University of California at San Francisco (total dose 4000-7000 cGy fractionated extending 2-3 weeks), Wara, et al, 35 reported nine cases of radiation-induced myelopathy. Three of nine patients experienced mild cervical cord-related neurological deficits without significant long-term symptoms.…”
Section: Discussionmentioning
confidence: 99%